Minimal clinically important difference for daily pedometer step count in COPD - Polgar, Oliver (ERJ Open Res, 2021)
Pedometer step count improves with pulmonary rehabilitation and deteriorates with time. The MCID for improvement and deterioration is 427 and −456 steps, respectively, but there is uncertainty about the reliability of these estimates. https://bit.ly/3ci97Jh